2021
DOI: 10.1016/j.solidstatesciences.2021.106732
|View full text |Cite
|
Sign up to set email alerts
|

Tuning thermoelectric properties of Bi2Ca2Co2Oy through K doping and laser floating zone processing

Abstract: In the present study, thermoelectric Bi2Ca2-xKxCo2Oy ceramic materials (x=0.0, 0.05, 0.075, 0.10, and 0.125) in different forms (called bulk, as-grown and annealed fibers) have been manufactured via a classical solid-state method and textured using the laser floating zone (LFZ) technique. The identification and characteristics of undoped and doped samples were determined by X-ray diffraction (XRD) and scanning electron microscopy (SEM). The XRD patterns of all samples have shown great similarity, and the major… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…It is already reported that the LFZ system improves the grain orientation in the materials causing an improvement of TE-parameters [16,24]. Lotgering factor (LF) is given with ( ) ( ) = --LF P P P P 0 0 formula, in which P is the sum of the peak intensities of preferred orientation, and P 0 is the sum of the peaks related to the randomly oriented grains [25,26].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is already reported that the LFZ system improves the grain orientation in the materials causing an improvement of TE-parameters [16,24]. Lotgering factor (LF) is given with ( ) ( ) = --LF P P P P 0 0 formula, in which P is the sum of the peak intensities of preferred orientation, and P 0 is the sum of the peaks related to the randomly oriented grains [25,26].…”
Section: Resultsmentioning
confidence: 99%
“…In previous works, Bi 2 Ca 2-x K x Co 2 O y with x=0, 0.05, 0.075, 0.10, and 0.125 thermoelectric materials were fabricated via the classical solid-state route, followed by laser floating zone (LFZ) texturing, then their high temperature thermoelectric properties were, in detail, investigated [16]. In this study, the results related to the microstructure, resistivity, Seebeck coefficient, thermal conductivity, and figure of merit, at low temperatures, will be presented, in order to evaluate the low temperature performances of these thermoelectric ceramics.…”
Section: Introductionmentioning
confidence: 99%